Matrix Country Club Sdn Bhd / Nur Husna Rosli - Rosli, Nur Husna (Faculty of Business and Management, 2023)
Welcome to my practical industry training journey. Everything that is told in this industrial report is through my observations and experience as a practical student at Matrix Country Club sdn. bhd. The experience of each practical student whom undergo the training may be different. However, the practical training journey that will be covered in this report shepherd you all the important points in the organization during my service for almost six months. However, the practical training journey that will be documented in this report will take you through all of the significant points in the organisation throughout my almost six-month tenure. My incredible adventure as an industrial training student will be detailed in phases, beginning with the student profile, company profile, SWOT analysis, discussion and recommendation, and lastly conclusion. May my practical training journey report provide readers with some substantial moral and cultural value. Thank you very much.